Poverty alleviation of the hard core poor in Bangladesh: a study on BRAC's income generation for vulnerable group development programme - Ahmed, Dilruba (BRAC, 2019)
BRAC launched IGVGO Programme to improve the condition of the poorest women covered by Vulnerable Groups Development (VGO) Programme. In this context high yielding variety (HYV) poultry birds rearing was introduced as an income generating activity for increasing the economic and nutritional well-being of the IGVGO participants. To sustain the process of development of the participants, BRAC merged IGVGO with Rural Development Programme (ROP). It is found that RDP could not include many of the very poor and disadvantaged women.